What Makes Small Firms Grow? : Finance, Human Capital, Technical Assistance, and the Business Environment in Romania - J. David Brown; John S. Earle; Dana Lup (Institute for the Study of Labor (IZA), 2004)
Although the development of a new private sector is generally considered crucial to economic transition, there has been rather little empirical research on the determinants of startup firm growth. This paper uses panel data techniques to analyze a survey of 297 new small enterprises in Romania containing detailed information from the startup date through 2001. We find strong evidence that access to external credit increases the growth of both employment and sales. Taxes appear to constrain growth. The data suggest that entrepreneurial skills have little independent effect on growth, once demand conditions are taken into account. The evidence for the effectiveness of technical assistance is weak: only assistance provided by foreign partners yields a positive effect. A wide variety of alternative measures of the business environment (contract enforcement, property rights, and corruption) are tested, but none are found to have any clear association with firm growth.
Keywords: P26; O16; M13; O19; 330; small firms; entrepreneurship; microfinance; business environment; Romania; Klein- und Mittelunternehmen; Unternehmenswachstum; Rumänien